Afucosylated Plasmodium falciparum-specific IgG is induced by infection but not by subunit vaccination - Mads Delbo Larsen (Nature Portfolio, 2021)
Here, Larsen et al. describe differences in Fc fucosylation of P. falciparum PfEMP1-specific IgG produced in response to natural infection versus VAR2CSA-type subunit vaccination, which leads to differences in the ability to induce FcγRIIIa-dependent natural killer cell degranulation.